ISLAMIC ECONOMICS AND FINANCE, THEN AND NOW: A FIQHĪ-CONOMIC PERSPECTIVE ON ITS DOCTRINES AND DEBATES - El-Sheikh, Salah (International Journal of Economics, Management and Accounting, 2013)
Each economy functions within a particular social framework, defined by its moral philosophy and legal system. What makes an economy Islamic is Shari'ah, the moral/legal discourses of the classical fuqaha, which defined the economy of classical Islam, shaped its micro and macro institutions, and modulated its actual performance. This economy, which was virtually effaced during the age of European colonialism, has become, in the post-colonial era, both a symbol and basis for revivalist movements in their attempts to re-Islamicize their economies and polities. Taking the economy of classical Islam and its fiqhi-conomic foundations as a point of departure and reference, this study generally aims at overviewing the salient features of the modern Islamic economy, its performance criteria and theoretical justification as envisioned in Islamic Economics, viewed as a science. In particular, it critically narrates the mainlines of the ongoing debate among Muslim scholars, and juxtaposes three main doctrinal approaches advanced by Muslim economists, viewed from the vantage point of efficiency and justice, the sine qua nonof that economy: namely, those of what I nominatively categorize as Reformist Traditionalists (Neo-Taqlidis), Islamic Modernists/Rationalists (Neo-Kalamis), and Neo-Conservative Muslim Secularists. In Section 1, I present a portrait of what I have called the fiqhi-economy of classical Islam: its philosophy of social harmony and related moral doctrine of economic justice as fairness ('adl qua qist), as well as its micro- and macro-economic institutions, and their underlying economic doctrine of socially embedded markets (suqs) à la Polanyi (1957). It serves as a backdrop for dialogically representing the modern (especially the post-colonial) debate on Islamic Economics, and Islamic finance, in the following sections: In section 2, the two polar disputational groups, the Reformist Traditionalists vs. the Muslim Secularists; in section 3, the Islamic Modernists; and in 4 the study concludes by delineating some fundamental commonalities and differences in their respective doctrinal positions. In general, the approach I follow is historicist and comparative-institutionalist; and the mainline argument follows the time-honored classical method of induction by example à laAristotle. As such, the study and its conclusions are bounded by the limitations of this methodology. JEL classification: B4, K00, N20, P5 Key words: Islamic economics, Islamic finance, Fiqhi-Conomic method